METAFORA ANTROPOMORFIK DALAM TUTURAN BAHAPAKAN KAKANAKAN PADA BAHASA BANJAR - Rissari Yayuk (Balai Bahasa Kalimantan Barat, 2018)
This research uses a qualitative descriptive method. The research problems are 1. How are the form and meaning of anthropomorphic metaphor image found in the speech of children in Banjar? 2. What politeness principle is violated in the speech hapakan (mockery) of children in Banjar language? The purpose of this research is to describe the form and meaning of anthropomorphic metaphor image found in the speech of hapakan (mockery) of children in Banjar. The benefit of this research is to develop a vision of Banjar Language for education and society in general, especially concerning to the problem of linguistic politeness. The technique used in this paper is the purposive sampling, the sampling technique of data source collection with consideration. The samples collected as data are three expressions that have the form and meaning of anthropomorphic metaphor. Stage of data analysis is data collection, data identification, classification, selection and interpretation. This stage must correspond to the theory. It is also interrelated each other. The results of data analysis are presented in plain words with technical terminology. The results of this study illustrate the forms and meanings of anthropomorphic metaphoric images found in the speech hapakan (mockery) of children in Banjar language including the word muha batimpap